Learning Through Visualising Solids with the Arloon Geometry Application : A Quantitative Study - Kanvaria, Vinod Kumar; Yadav, Archana (JOURNAL OF INDIAN EDUCATION, 2023)
In India, the use of augmented reality technology in the teaching-learning process of mathematics is in its early stages. The present study aimed to utilise the potential of the augmented reality-based android application The Arloon Geometry to improve the achievement of learners in the concept of visualising solids. A total of 500 Grade VIII learners participated in the quasi-experimental study. The results of the study allowed us to reject the null hypothesis and accept the alternate hypothesis that there is a significant difference in learning achievement of visualisation skills of learners when the application Arloon Geometry was used to visualise solids. The study recommends integrating augmented reality technology across various disciplines to improve the achievement level of learners.